Factors Driving Internet Banking Adoption in Guyana: A Study of Developing Countries - Sarran, Dave; Mohammed, Ibrahim; DeFreitas, Penelope (Journal of Information System and Informatics, 2025)
Internet banking across banking institutions has grown tremendously in popularity over the past two decades. Internet banking among customers remains a crucial challenge within the banking industry, especially in developing countries. As such, this research investigates the factors affecting internet banking adoption in Guyana by extending the Technology Acceptance Model (TAM) to include information quality, service quality, system quality and computer self-efficacy as predictor variables. The study evaluated hypotheses that these variables influence users’ perceived ease of use and perceived usefulness, which in turn affect actual usage of internet banking services. Data from 160 internet banking customers was collected and analysed using the Structural Equation Modelling (SEM) approach to test eight (8) hypotheses among constructs of the extended TAM model. The findings of the study suggest that service quality positively affects consumers’ perceived ease of use of Internet banking, while computer self-efficacy positively affects consumers’ perceived usefulness to adopt Internet banking. The findings also demonstrated that both perceived ease of use and perceived usefulness significantly impacted the actual usage of Internet banking. The findings of this study offer Guyanese banking institutions useful information, emphasizing the necessity of enhancing service quality standards and funding digital literacy programs to increase the adoption of online banking services.